A bifunctional metal–organic framework featuring the combination of open metal sites and Lewis basic sites for selective gas adsorption and heterogeneous cascade catalysis. Issue 39 (21st September 2016) - He, Hongming; Sun, Fuxing; Aguila, Briana; Perman, Jason A.; Ma, Shengqian; Zhu, Guangshan
Abstract : A bifunctional MOF featuring the combination of open metal sites (Zn 2+ ) and Lewis basic sites (–NH2 ) has been constructed for selective gas adsorption and heterogeneous cascade catalysis. Abstract : A bifunctional MOF (JUC-199) featuring dual functionality, open metal sites (Zn 2+ ) and Lewis basic sites (–NH2 ), has been successfully synthesized using a custom-designed ligand. JUC-199 demonstrated good selective gas sorption behaviours with IAST selectivity values of 9, 30, 37 and 64 at 298 K and 101 kPa for CO2 /CH4, CO2 /N2, C2 H6 /CH4 and C2 H4 /CH4 respectively; surpassing those of most MOFs reported thus far. Moreover, JUC-199 can serve as a heterogeneous cascade catalyst to efficiently catalyse the tandem one-pot deacatalization-Knoevenagel condensation reaction.